Jurnal Ilmiah Pekerjaan Sosial: Pengasuhan Anak oleh Perempuan Rawan Sosial Ekonomi di Kecamatan Pedurungan Kota Semarang - Vidya, Annes; Pribowo, Pribowo; Widiansyah, Wiwit (Pekerjaan Sosial, 2025)
This research was conducted in Pedurungan District against the background of the phenomenon of inappropriate child care. This research aims to examine and describe childcare by socio-economically vulnerable women in Pedurungan District, Semarang City, which is studied through the aspects of parental responsiveness and parental demandingness. The method used in this research is a case study with a qualitative approach. The primary data source for this research is data obtained by researchers through interviews and observations, while the secondary data source for this research was obtained through documentation studies and other documents relevant to the research topic. The informants for this research are socio-economically vulnerable women in Pedurungan District who have 7 dependent children and 7 people in the PRSE neighborhood. Checking the validity of the data in this research uses credibility, transferability, dependability and confirmability. The research results show that there are still problems in fulfilling the emotional needs between a caregiver (PRSE) and a child which is caused by PRSE's lack of knowledge about parenting and PRSE's lack of skills in managing emotions. The results of this research indicate that there is a need for education and counseling regarding parenting and developing PRSE emotion management skills. Based on the results of this research, the researchers designed a program, namely a program called Sinar Cerah using the Social Group Work method.